Embracing the Philosophy of Responsible Citizenship - On a Path to Ukraine's Societal Transformation - Svyrydenko, Denys; Revin, Frol (Studia Warmińskie, 2023)
In the European educational paradigm, the philosophy of the responsible citizenship assumes a central role in shaping the future of diverse and interconnected societies. This article explores how European educational systems have been designed to instill values of civic engagement, respect for others, and environmental awareness, equipping EU citizens with the tools they need to become responsible and active members of the global community. The article further examines how the integration of sustainable development and environmental education empowers young minds to become advocates for environmental preservation and guardians of rational planet-wide stewardship. In particular, by highlighting the successes, challenges, and ongoing efforts within the European educational paradigm, we aim to shed light on how responsible citizenship approaches can lead to more inclusive and cohesive societies that thrive on empathy, tolerance, and solidarity both in Ukraine and globally. This point directly corresponds and is clearly reflected in the report of the European commission on science education highlighting the crucial need for an educational platform to be put in place that would be able to nurture, cultivate and disseminate the values and the critical role that a scientifically-minded, eco-conscious citizenry has on the shaping of our shared global future. Hence, we can conclude that as Ukrainian nation aspires to build a more inclusive and forward-looking society, the philosophy of responsible citizenship promoted within the European educational paradigm offers valuable insights and tools to equip, modernize and revitalize our system of education. By embracing responsible citizenship philosophy, Ukraine can effectively address the challenges (e.g. the environmental, social and economic effects of the on-going war with Russia, incompetent bureaucracy and civil service, stagnant social institutions, inadequate levels of civic engagement and ineffective social management) it faces while providing its population with a sure roadmap to becoming active agents of positive change in the drastically volatile and interrelated global village.